Pendidikan Terkait Pewarnaan Kain Batik: Warna yang Dihasilkan oleh Zat Warna Alam - Daru Anggara Murty; Maghfiroh Maghfiroh; Zahir Widadi; Faiz Tyas Hanifah (Departement of Mathematics Education, 2024)
This study aims to provide education on batik dyeing, specifically focusing on the colors produced by natural dyes. It employs an experimental approach to evaluate the effectiveness of various fixatives in dyeing cotton fabric with natural dye from secang wood. Conducted in a laboratory, the research involves dyeing cotton fabric with natural dye from coconut husk and testing three types of fixatives: alum, tannin, and lime. Data were collected through visual observation of color intensity, color fastness testing using grey scale, and color direction analysis with Coloor.co. The variables tested include the type of fixative (independent variable) and color quality (intensity, color fastness, color direction) as dependent variables. Control variables include dye concentration, sample volume, and measurement conditions. Analysis results show that natural dye from coconut husk produces a brownish color. Batik production with natural dye from coconut husk yields a consistent color sequence: light brown with alum as the fixative, slight color change with lime as the second fixative, and the darkest color with tannin as the fixative. These colors fall into the warm and vintage categories according to the Coloors.co application, both before and after washing.